Closing the gap by increasing access to clinical dietetic services for urban Aboriginal and Torres Strait Islander people. Issue 4 (13th November 2013) - Foley, Wendy; Houston, Annalie
Abstract Aim Late in 2010, the dietetic clinic in a Brisbane Indigenous health service increased from one to four days/week. This article presents research to assess the impact of this on access for urban Aboriginal and Torres Strait Islander people to dietetic services. Methods Clinic data on referrals and attendance before and after this change are compared. Focus groups with staff and in‐depth interviews with 13 patients were conducted to ascertain staff and patient experiences of the clinic changes. Results The additional time allowed the dietitian to develop a stronger presence in the community and clinic. This ensured that the dietetic service was culturally safe for clients and strengthened team approaches to patient care in the clinic. Despite space limitations, new referrals more than doubled and occasions of service tripled. New patients were more likely to attend an appointment with the dietitian in 2011 than in 2010 (P < 0.001) and the proportion of patients who did not attend appointments without rescheduling decreased significantly (P = 0.006). Conclusions Various factors contributed to improved access for Aboriginal and Torres Strait Islander people to dietetic care. These included fostering the dietitian's cultural awareness and building trust with Indigenous community members, making the dietetic service culturally safe for clients; connecting with patients through appropriate communication styles and inter‐professional teamwork. Providing an expanded and culturally safe dietetic service improved the availability, acceptability and appropriateness for Aboriginal and Torres Strait Islander people.